Implementasi Pembelajaran Fiqih Materi Wudhu di Kelas VII MTs Al-Islam Kemuja Kecamatan Mendo Barat - Aripin, Zahrial; Noor, Wahyudin; Tujuh, Syarifah HR Daeng; Sumar, Sumar (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This research aims to describe the implementation of fiqh thaharah learning about ablution material, as well as explaining the supporting and inhibiting factors in the process of implementing fiqh learning about ablution material in class VII Mts Al-Islam Kemuja, West Mendo District. This research is a type of descriptive qualitative research, where this qualitative research describes a detailed explanation of the phenomenon. Data was collected by observing, interviewing and documenting. Next, it is analyzed by collecting data, summarizing, presenting data and drawing conclusions. The results of this research can be concluded that the implementation of Islamic jurisprudence learning about ablution material is carried out in three stages, namely the learning planning stage, the learning implementation stage, and the learning outcomes evaluation stage. The supporting and inhibiting factors in the implementation of fiqh learning are first, supporting factors from educators, namely looking at the ability and quality of an educator in delivering professional teaching, and in terms of adequate facilities and infrastructure to support the learning process. Second, inhibiting factors consisting of students, starting from interest in learning, physical condition, discipline and activities. And in the learning environment situation.